Africa’s youth: ticking time bomb or an opportunity? - Kingsley Ighobor (Africa Renewal, 2013)
Senegalese opposition politicians denounced the country’s high unemployment rate to mobilize youth against former President Abdoulaye Wade in the country’s 2012 presidential election. Joblessness was one of the main issues that drove the country’s many young people into the streets and to the voting stations to press for a change of government. At least six people died in the protests, and President Wade was defeated by the current leader, Macky Sall.